Characterization of the cognitive processes related to directed attention in natural environments and their relationship with physical activity. A review on university students - Baena-Morales, S.; González-Fernández, F.T.; García-Taibo, O.; López-Morales, J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
The aim of the present work is to review the bibliography that has compared the effect of physical activity (PA) performed in different environments, such as natural (AFMN) and artificial (AFEA), on directed attention (SA). For this purpose, a search has been made in different databases such as PubMed, Google academic and Sports DISCUS. All the searches were done from January 2000 to December 2019 using keywords such as directed attention, green exercise, physical activity or university students. In addition, articles were excluded if the population was not exclusively university students or if methodological did not specify variables such as the type of exercise performed or the AS measurement test. A total of six articles were selected which fully met the inclusion criteria. From the analysis of these investigations it was concluded that the effect of the AFMN is not significatively greater than the AEFA on the SA. Several methodological improvements are recommended for future research.